Levodopa exposure and nigral neuroinflammation in parkinsonian disorders: A postmortem study of 63 cases - Backman, Emmilotta A.; Luntamo, Laura; Vahlberg, Tero; Gardberg, Maria; Kaasinen, Valtteri (Springer Nature, 2026)
Levodopa remains the cornerstone of treatment in Parkinson’s disease (PD), but its long-term impact on neuroinflammation remains unclear, particularly in multiple system atrophy (MSA) and progressive supranuclear palsy (PSP), where levodopa efficacy is limited. This study examined whether chronic levodopa exposure is associated with neuroinflammation or dopaminergic neuronal loss in end-stage PD, MSA, and PSP. Postmortem midbrain tissue from 63 neuropathologically confirmed cases (PD: n = 38; PSP: n = 13; MSA: n = 12) was analyzed. Immunohistochemistry was used to quantify tyrosine hydroxylase positive (TH+) neurons in the substantia nigra pars compacta (SNc), along with T lymphocyte (CD3+, CD4+, CD8+) infiltration and microglial density (Iba1 expression). Levodopa exposure was estimated using three models and analyzed in relation to neuropathological markers, adjusting for age at death, sex, disease duration, and Hoehn & Yahr stage. Results. No significant associations were observed between levodopa exposure and TH + neuronal density or T cell infiltration or microglial density. For example, in PD, mean daily levodopa dose was not associated with CD3 + T cell density (β = 2.06 × 10⁻⁵, 95%CI: −0.001 to 0.001, p = 0.96). Chronic levodopa use was not associated with persistent neuroinflammation or dopaminergic neuronal loss at end-stage disease, suggesting no long-term immune-mediated toxicity in the substantia nigra.